IMPLEMENTASI STRATEGI PENGELOLAAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP DI TEMPAT PEMBUANGAN AKHIR TRANSLIK PASIR PANJANG - Hasaruddin Hasaruddin (Bajang Institute, 2022)
This research was conducted in December 2020 at the village of Pasir Panjang, West Kotawaringin Regency, the method used in this research was the survey method. This research uses a qualitative approach, with data analysis techniques used are interviews and observation. The research subjects were determined purvosively, namely: (1). The leaders and responsibilities of the TPA, (2). Community members. Based on the description of the research data, the following can be concluded: Waste management in this Long Sand Translik landfill uses sanitary landfill methods.Waste management in this TPA Translik Pasir Panjang is: 1). Transportation of waste, 2). Sanitary landfill process in Long Sand Translic Landfill, namely: Storage zone, Work surface, Waste demolition, Driver, spread, and leveling of waste, Soil cover, Lindi Management, Lindi Processing, Lindi Resiculation, Gas Processing, and Gas Control. The composition of the waste in the TPA is dominated by 50% organic waste, 8% paper waste, 1% glass waste, 15% plastic waste, 2% metal waste, 2% wood waste, 2% cloth waste, 1% rubber waste, and 19% other waste. The impact of waste management at the TPA Translik is in empowering local communities, especially for scavengers or collectors. Negative impact of this TPA, there have been no complaints from the local community about the smell or things related to waste management at the TPA Translik